2008
DOI: 10.1093/molehr/gan082
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression microarray profiles of cumulus cells in lean and overweight-obese polycystic ovary syndrome patients

Abstract: The aim of this work was to study gene expression patterns of cultured cumulus cells from lean and overweight-obese polycystic ovary syndrome (PCOS) patients using genome-wide oligonucleotide microarray. The study included 25 patients undergoing in vitro fertilization and intra-cytoplasmic sperm injection: 12 diagnosed with PCOS and 13 matching controls. Each of the groups was subdivided into lean (body mass index (BMI) < 24) and overweight (BMI > 27) subgroups. The following comparisons of gene expression dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 33 publications
4
83
3
3
Order By: Relevance
“…In this study, 623 lncRNAs and 260 mRNAs were differentially expressed between CC samples from PCOS and normal patients. The differentially expressed mRNAs (n=260) isolated in this study were not identical to those published in previous reports [2,13]. This difference may be due to differences in the samples (oocyte, ovarian tissue, or cumulus cells) and the gene chips between ours and the previous studies.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…In this study, 623 lncRNAs and 260 mRNAs were differentially expressed between CC samples from PCOS and normal patients. The differentially expressed mRNAs (n=260) isolated in this study were not identical to those published in previous reports [2,13]. This difference may be due to differences in the samples (oocyte, ovarian tissue, or cumulus cells) and the gene chips between ours and the previous studies.…”
Section: Discussioncontrasting
confidence: 65%
“…This difference may be due to differences in the samples (oocyte, ovarian tissue, or cumulus cells) and the gene chips between ours and the previous studies. Notably, because previous reports have shown that the lean PCOS group is the source of the unique characteristics of Bauthentic^PCOS and obesity may be regarded as modifier of the syndrome or as a separate pathological mechanism that results in similar consequences [13], we selected lean PCOS patients with lower BMI (21.6±1.5) in this study to reduce the differences in gene expression caused by obesity. In fact, PCOS in lean and obese individuals should be regarded as separate subentities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations were further supported by subsequent studies that measured global gene expression of cumulus cells, which was concluded to be a non-invasive test for oocyte/embryo quality [2,3,15,41]. Granulosa and cumulus cell gene expression profiling has also been used to compare the effects of recombinant FSH vs. human menopausal gonadotrophin (hMG) [6,14], floating vs. cumulus granulosa cells [22], cumulus cells from lean vs. overweight-obese PCOS patients [21], and ovarian reserve status in young women with diminished ovarian reserve [39].…”
Section: Introductionmentioning
confidence: 87%
“…Patient BMI alters CC gene expression in both polycystic ovarian syndrome (PCOS) (Kenigsberg et al 2009) and non-PCOS women (Robker et al 2009). Therefore, studies with a large range of ages or BMIs may show DRGE profiles that would not exist if the age ranges or BMI were controlled for in the studies.…”
Section: Variables Affecting Granulosa Cell Transcriptomic Profiles Omentioning
confidence: 99%